Mechanistic Insights into the Enhancement of Natural Dyeability of PLA Fabrics via Atmospheric DBD Plasma Treatment - Chouytan, Jadsadaporn; Suwankosit, Arisara; Rattanapan, Suwat; Udon, Somchai (Trends in Sciences, 2026)
Poly(lactic acid) (PLA) is a biodegradable and environmentally sustainable material, although its ability for dyeing is limited, especially with natural dyes. This study examined the application of dielectric barrier discharge (DBD) plasma in atmospheric conditions to enhance the surface features of PLA fabrics without using wetting agents. Experiments utilized the response surface methodology (RSM) analysis for determining the proper condition, including power and plasma exposure time. X-ray photoelectron spectroscopy (XPS) analysis revealed an increase in the O/C ratio from ~0.42 to ~0.59 after 30 s of plasma exposure, while field emission scanning electron microscopy (FE-SEM) images expressed the appearance of nanoscale roughness over the entire fiber surface due to plasma etching. Furthermore, the water uptake increased about 2.5 times, indicating a change in the surface characteristics toward increased hydrophilicity. To analyze the dyeing performance, the Fickian model was used to evaluate the dye diffusion coefficient (D), along with calculating the color strength (K/S). It was found that relatively higher polar dyes like henna and lac exhibited significantly improved dye adhesion, while turmeric and annatto showed only minor changes. The washing fastness results supported this observation; henna and lac maintained stronger color adhesion after treatment, whereas turmeric and annatto showed only modest improvement. Mechanical property tests revealed a slight decrease in yarn strength with prolonged plasma treatment. In conclusion, the pretreatment of PLA fabric with DBD plasma is a clean, chemical-free, and effective method to enhance the dyeing properties of PLA fabric with natural dyes, especially those with relatively higher polarity, if exposure time is controlled within an appropriate range. HIGHLIGHTS Atmospheric DBD plasma unlocked the inert surface of PLA, resulting in functional sites that allow natural dyes to penetrate and bond without the use of mordants. The treatment achieved a balance between nanoscale etching and oxidation, reaching a critical activation point where hydrophilicity and mechanical strength coexist. This work bridges the gap between green processing and performance, providing a scalable route for naturally dyed biobased textiles with long-term color stability. GRAPHICAL ABSTRACT